Rentabilidad de la empresa REYBANPAC de la parroquia San Juan en el periodo 2023. - Recillo Quinto, Briggitte Edith (2024)
This case study titled "Profitability of the REYBANPAC company in the San Juan parish in the periods 2022-2023" focuses on evaluating the company's financial situation, with the aim of identifying the causes behind the net profit decrease and its impact on financial performance. The analysis is justified by the importance of understanding the efficiency of financial management to ensure REYBANPAC's sustainability and growth. The methodology employed combines qualitative and quantitative approaches, using techniques such as document review of financial statements and the application of financial indicators. The results reveal an increase in total assets, but also a rise in provisions for uncollectible accounts and deterioration, and an increase in total liabilities that could impact the company's liquidity. In terms of profitability, all key indicators showed a significant decrease, reflecting lower efficiency in generating gross and net profits, and in the use of assets and equity. The conclusions highlight a negative trend in REYBANPAC's economic performance, emphasizing the need to review operational and financial strategies to improve future profitability.